On New Conservation Laws of Fin Equation - Gülden Gün Polat; Özlem Orhan; Teoman Özer (Advances in Mathematical Physics)
We study the new conservation forms of the nonlinear fin equation in mathematical physics. In this study, first, Lie point symmetries of the fin equation are identified and classified. Then by using the relationship of Lie symmetry and λ-symmetry, new λ-functions are investigated. In addition, the Jacobi Last Multiplier method and the approach, which is based on the fact λ-functions are assumed to be of linear form, are considered as different procedures for lambda symmetry analysis. Finally, the corresponding new conservation laws and invariant solutions of the equation are presented.